Primary Small Bowel GIST Presenting as a Life-Threatening Emergency: A Report of Two Cases. (28th March 2017) - Khuri, Safi; Gilshtein, Hayim; Darawshy, Abd-alkarim; Bahouth, Hany; Kluger, Yoram
Abstract : Gastrointestinal stromal tumor (GIST) is a rare stromal neoplasm, which represents the most common mesenchymal tumor of the gastrointestinal tract. It is characterized by indolent clinical symptoms, although it can present as a life-threatening emergency. Herein, we present two cases of primary small bowel GIST treated at our department. A 68-year-old female patient presented to our emergency department with a diffuse abdominal pain of acute onset. Imaging studies revealed a mass at proximal jejunum, with a nearby free air and fluid. At surgery, a mass of 9 cm was found at proximal jejunum, 3 cm distal to the treitz ligament, with perforation on the lateral wall of the mass. En bloc resection was performed. Pathology report was positive for gastrointestinal stromal tumor. A 70-year-old male patient presented to our emergency department with 3 days of dark tarry stool and few hours of hematochezia. Computed tomography angiography revealed a mass at the pelvis, with calcifications, attached to the distal ileum, with intraluminal blush of intravenous iodine. At surgery, a mass of 8 cm at the distal ileum was found. Resection of the mass along with a 20 cm of ileum was completed. Histopathology report was positive for malignant gastrointestinal stromal tumor.